2020
DOI: 10.5415/apallergy.2020.10.e14
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of eosinophilic inflammation

Abstract: Eosinophils play roles in the pathogenesis of various diseases. In order to accumulate within sites of inflammation, eosinophils must adhere to, and migrate across the microvasculature. These processes are largely controlled by type 2-immune responses; interleukin (IL)-4 and IL-13 induce the expression of endothelial adhesion molecule vascular cell adhesion molecule-1 (VCAM-1), a representative adhesive ligand for eosinophils, while also stimulating generations of CC chemokines from structural cells, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 66 publications
1
31
0
Order By: Relevance
“…IL-31 has also been reported to be involved in Th2-mediated diseases, such as allergic diseases, as well as KD ( 32 ). Eosinophils play an important role in type 2 inflammation ( 33 ). Previous studies have reported that patients with KD had higher eosinophils, Th2 cytokines IL-4, IL-5, and eosinophil cationic protein (ECP) levels than controls ( 17 , 25 ).…”
Section: Abnormal Type 2 Inflammation Imbalance T Helper Type 17/regmentioning
confidence: 99%
“…IL-31 has also been reported to be involved in Th2-mediated diseases, such as allergic diseases, as well as KD ( 32 ). Eosinophils play an important role in type 2 inflammation ( 33 ). Previous studies have reported that patients with KD had higher eosinophils, Th2 cytokines IL-4, IL-5, and eosinophil cationic protein (ECP) levels than controls ( 17 , 25 ).…”
Section: Abnormal Type 2 Inflammation Imbalance T Helper Type 17/regmentioning
confidence: 99%
“…While in healthy subjects the number of eosinophils in the peripheral blood is low, it can increase dramatically under pathophysiological conditions such as atopic dermatitis, bronchial asthma, eosinophilic esophagitis, gastritis, gastroenteritis, colitis or hematological malignancies ( 54 , 62 , 71 , 80 , 123 ). The large body of evidence supporting the critical role of eosinophils in parasitic and inflammatory diseases has prompted and intensified investigations on potential targets to modulate cellular responses of eosinophils.…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophils themselves produce different cytokines including IL-1, IL-3, IL-4, IL-5, IL-6, IL-8, TNF-α, TGF-β, GM-CSF and pro-inflammatory mediators such as leukotriene C4 (LTC4), platelet-activation factor (PAF) ( 71 , 74 ), the granular cationic proteins, major basic protein (MBP) 1, MBP 2, eosinophil cationic protein (ECP), eosinophil-derived neurotoxin (EDN) and eosinophil peroxidase (EPO). MBP which is present in the crystal core of the specific granules has cytotoxic effects due to interference with electrical properties and permeability of the cell membrane.…”
Section: Eosinophil Granulocytesmentioning
confidence: 99%
“…NOD2 ligand MDP can activate BEAS-2B cells and human basophils by stimulating their release of inflammatory cytokines, including Th17-polarizing IL-6, and upregulating the expression of intercellular adhesion molecule (ICAM)-1 and vascular cell adhesion molecule (VCAM)-1 in the co-culture of basophils and bronchial epithelial cells through NF-κB, c-Jun N-terminal kinases (JNK) and p38 MAPK pathways [12]; hence, magnifying the inflammatory response. ICAM-1 and VCAM-1 are essential for leucocytes migration to the inflammatory sites in allergy, with expressions that are positively correlated with allergic asthma severity [12,108]. MDP can also induce the release of antimicrobial peptide β-defensin 2 from the bronchial epithelial cells in the co-culture of human basophils and human bronchial epithelial cells [12].…”
Section: Nlr Of Basophils and Bacterial Infection In Allergic Asthmamentioning
confidence: 99%